Analisis Potensi Pajak Restoran dalam Peningkatan Penerimaan Pajak Daerah di Kota Surabaya - Karina Eka Wardani; Oryza Tannar (Universitas Veteran Bangun Nusantara, 2025)
This study aims to evaluate the potential of restaurant tax in contributing to the increase of Local Own-Source Revenue (PAD) in Surabaya City by analyzing the alignment between tax targets and actual revenues during the period of 2022 to 2025. A descriptive qualitative approach was employed, utilizing a case study at the Surabaya Revenue Agency (BAPENDA). Data were collected through triangulation methods, including interviews with relevant stakeholders and document analysis. The findings reveal fluctuations in restaurant tax realization, with the highest achievements recorded in 2023 (95.47%) and 2024 (102.74%). The average annual growth rate of 15.67% indicates significant potential for revenue expansion in this sector. However, several challenges affect the effectiveness of tax collection, such as low taxpayer awareness, an insufficient number of field officers, and suboptimal implementation of digital reporting systems. In response, BAPENDA has undertaken various initiatives, including taxpayer education and outreach programs, data updating efforts, and strengthening of monitoring mechanisms. This research highlights the importance of integrating digital technologies, enhancing institutional capacity, and promoting tax literacy as key strategies to optimize the contribution of the restaurant sector to PAD. The findings provide valuable insights for formulating sustainable, locally based fiscal policies